2017
DOI: 10.1038/srep39710
|View full text |Cite|
|
Sign up to set email alerts
|

Common Variable Immunodeficiency patients with a phenotypic profile of immunosenescence present with thrombocytopenia

Abstract: Common variable immunodeficiency (CVID) is a heterogeneous group of diseases. Our aim was to define sub-groups of CVID patients with similar phenotypes and clinical characteristics. Using eight-color flow cytometry, we analyzed both B- and T-cell phenotypes in a cohort of 88 CVID patients and 48 healthy donors. A hierarchical clustering of probability binning “bins” yielded a separate cluster of 22 CVID patients with an abnormal phenotype. We showed coordinated proportional changes in naïve CD4+ T-cells (decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Not surprisingly, manual analysis influences the end result to a great extent. To complicate the matter, particular diseases present with high proportions of subsets that are very rare in healthy (4,5) necessitating disease specific benchmarking. 1A), but would yield larger discrepancy in CD8+ T-cells (Fig.…”
Section: Why At What Level and To What Extent We Need Reproducibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Not surprisingly, manual analysis influences the end result to a great extent. To complicate the matter, particular diseases present with high proportions of subsets that are very rare in healthy (4,5) necessitating disease specific benchmarking. 1A), but would yield larger discrepancy in CD8+ T-cells (Fig.…”
Section: Why At What Level and To What Extent We Need Reproducibilitymentioning
confidence: 99%
“…1B), stressing the need for subset specific benchmarking. To complicate the matter, particular diseases present with high proportions of subsets that are very rare in healthy (4,5) necessitating disease specific benchmarking. Definitions that influence staining patterns may impact the ability to clearly define and/or resolve particular subsets, which in turn will impact enumeration.…”
Section: Why At What Level and To What Extent We Need Reproducibilitymentioning
confidence: 99%
“…The pathogenic mechanism of rheumatologic diseases in CVID is not yet recognized. However, increased autoreactive B cell such as CD21 low B cell, autoantibodies, reduced number of regulatory T cells (Tregs) and abnormalities in cytokine production may result in autoimmune conditions and rheumatologic diseases . Moreover, decreased IL‐10‐producing regulatory B cells (which play an important role in the development of Tregs and peripheral tolerance) have been reported in patients with CVID.…”
Section: Introductionmentioning
confidence: 99%
“…CVID is a heterogeneous disease, which is associated with recurrent and severe infections and characterized by deficiencies in antibody production. Previous studies have shown that there are subgroups of patients with CVID with respect to their genotype, B cell or T cell profiles and clinical phenotypes [10][11][12][13][14][15][16]. Most CVID patients receive immunoglobulin (Ig)G substitution, which has a significant impact on health-related quality of life [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Most CVID patients receive immunoglobulin (Ig)G substitution, which has a significant impact on health-related quality of life [8,9]. Previous studies have shown that there are subgroups of patients with CVID with respect to their genotype, B cell or T cell profiles and clinical phenotypes [10][11][12][13][14][15][16]. However, very few studies analyzing the heterogeneity of CVID go beyond biomedical perspectives and focus on the psychosocial aspects of the disease including perceived health.…”
Section: Introductionmentioning
confidence: 99%